Reduksi Kandungan Logam Berat dalam Limbah Cair Industri Eektroplating dengan Menggunakan Proses Elektrokoagulasi - Bambang Hari Prabowo; Giovana Ghasary Putri; Muhamad Faisal Sadikin (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
The content of heavy metals in the electroplating industry wastewater that is not controlled can damage the environment and has a negative impact on human health. Electroplating wastewater disposal should not throw into the environment because heavy metals are toxic and dangerous. In this research, we are using electrocoagulation method for reduce the content of heavy metals in the electroplating wastewater (Cr, Ni and Fe). Electroplating industrial wastewater is containing heavy metals from the coating structure of electrolyte solution and rinsing results of electroplating method that wastewater contain high heavy metals. Research by electrocoagulation method is applied to determine how much reduction in metal waste electroplating industry. Parameters changed in this research is the current flowing (2,5 ampere and 5 ampere) and the addition of NaOH. In this research, electrocoagulation process use 4,5 L of wastewater. Samples were taken and analyzed at the condition of 10, 20, 30, 40 and 50 minutes. Results from this research is reduction content of heavy metals 89,55% Cr, 99,52% Fe and 98,93% Ni. Reduction that achieved based on regulatory environment ministry is Fe and Ni.